Public Health Research Priorities to Address Female Genital Mutilation or Cutting in the United States - Atkinson, Holly G. (Am J Public Health, 2019)
Female genital mutilation or cutting (FGM/C), an age-old tradition that is still widely practiced around the world, is gaining recognition as an important public health issue in the United States. Increasingly, because of migration, women and girls affected by FGM/C have become members of host communities where the practice is not culturally acceptable. According to recent conservative estimates, more than 513 000 immigrant women and girls living in the United States have undergone or are at risk for FGM/C, a significant increase from the 1990 estimate of 168 000. The arrests of physicians in Michigan in 2017 for performing FGM/C on minors underscores the fact that cutting is happening in the United States. We have identified numerous gaps in our understanding of the magnitude of the problem in the United States and in the availability of scientific data informing a variety of interventions (preventive, clinical, educational, legal). We catalog these major gaps and propose a research agenda that can help public health experts, researchers, clinicians, and other stakeholders to establish priorities as we confront FGM/C as an important health issue affecting hundreds of thousands of women and girls in the United States.